Pengaruh Gaya Kepemimpinan Terhadap Kinerja Pegawai Pada Kantor Kecamatan Jambi Timur Kota Jambi - Kulawu Kulawu (Universitas Batanghari Jambi, 2019)
The purpose of this study was to describe the leadership style and the performance of the employees of the Kantor Kecamatan Jambi Timur Kota Jambi and to analyse the influence of leadership styles on performance clerk on Kantor Kecamatan Jambi Timur Kota Jambi. This research is a desciptive quantitative research and analysis tool used in this research are simple linear regression is useful to see the direction of the relationship between the variable bound against free. For the purpose of answering the purpose number 2 used statistical F test and test t. The correlation coefficient to know how the relationship between variables and coefficients of determination of useful to see the magnitude of the influence of the variable bound against free. Kantor Kecamatan Jambi Timur Kota Jambi is a functional unit that functions as a Center for community service diwilayKantor sub district East of the city of Jambi Jambi which is a functional unit that functions as a service centre relic community work fostering the role of the region as well as communities it works in order to improve the ability of kesejatheraan life and provide maximum service thoroughly integrated to the society and the region it works. wrong the only form of Jambi Timur Subdistrict Office activities the city of Jambi is doing a service to the community. Ah work fostering the role of the region as well as communities it works in order to improve the ability of kesejatheraan life and provide maximum service thoroughly integrated to the society and the region it works. one form of activity Subdistrict offices East of the city of Jambi Jambi is doing a service to the community. The average score of 148.5 means leadership style at the Kantor Kecamatan Jambi Timur Kota Jambi are on a very high criteria based on the assessment of employees. The average score of 130.4 means high performance dimensions assessed by the clerk of the Kantor Kecamatan Jambi Timur Kota Jambi. The value t calculate of 3,979 is greater than the value of the t table of 2,036, with significant value which is smaller than the alpha (0.000 < 0.05). This means that the hypothesis stating that influential positive leadership style against the performance of employees. Based on the conclusions above, then the author can give you some advice that leadership style affects performance, therefore the leadership must adopt the attitude of leadership style is good, because it will improve the performance of employees and the lowest Indicators on a leadership style that is the number of leadership ability in solving problems, thus the leadership must learn what strategies should be used in solving masalahd alam organsasi, for if this indicator rated high by an employee then the employees will work more effectively.